Shallow Water Bathymetry Estimation with Landsat 8 Imagery: Band Ratio Application Method in Karimunjawa Waters, Central Jawa, Indonesia - Luhur Moekti Prayogo; Abdul Basith (Jurnal Geospasial Indonesia, 2026)
Bathymetric data are essential for producing water-depth maps and supporting navigational safety. The Karimunjawa Islands were selected as the study area because they are characterized by shallow waters, complex coastal ecosystems, and active marine tourism and navigation activities that require accurate and up-to-date depth information. This study aimed to estimate shallow-water depth using Landsat 8 imagery with the band ratio method. The visible bands used in this study included blue, green, and red bands, with blue/red, green/red, and blue/green ratio combinations. Field-measured depth data were used as reference data to evaluate the bathymetric estimation results. The findings showed that the blue/red ratio produced the smallest depth difference within the 0–5 m depth range. The next best results were obtained from the green/red and blue/green ratios. The better performance of the blue/red ratio was likely influenced by local water conditions, in which the contrast between the blue band, which can penetrate the water column, and the red band, which attenuates more rapidly, was able to represent depth variations more effectively. However, this study was limited to the use of Landsat 8 imagery with a spatial resolution of 30 m, selected visible-band combinations, and did not examine in detail the effects of bottom substrate variation and water quality. The accuracy of the estimation also decreased with increasing depth. Therefore, the best band combination for shallow-water bathymetric estimation may vary depending on water conditions, bottom characteristics, image quality, and processing methods, so the results of this study cannot be directly generalized to all aquatic areas.